Preparation and characterization of ZnO/ZnAl₂O₄-mixed metal oxides for dye-sensitized photodetector using Zn/Al-layered double hydroxide as precursor - Salih, Ethar Yahya; Mohd Sabri, Mohd Faizul; Tan, Sin Tee; Sulaiman, Khaulah; Hussein, Mohd Zobir; Mohd Said, Suhana; Chi, Chin Yap (Springer Netherlands, 2019)
In this article, a simple new technique has been developed for the preparation of ZnO/ZnAl₂O₄-mixed metal oxide (MMO) as anode materials for visible light dye-sensitized (DS) photodetector using Zn/Al-layered double hydroxide (LDH) as precursor. Subsequently, a detailed correlation between the structural properties of the prepared samples and the photo-responsive behavior of the fabricated DS photodetectors was elucidated. Specifically, it is evidenced that a high surface area of the prepared mesoporous MMO anode materials exhibit excellent dye absorptivity and thus facilitate free electron transfer and increase the photocurrent in the fabricated DS photodetector. A significant bathochromic shift was observed in the optical energy of the prepared MMO samples under the increment of molar ratio, providing a short electron transfer pathway in the optimized Z7A DS photodetector, which in turn demonstrated photo-responsivity and photo-detectivity of 6 mA/W and 1.7 × 10⁺¹⁰ Jones, respectively. This work presents an alternative approach for the design of an eco-friendly MMO-based DS photodetector.